Association between the immune-inflammation index and the severity and clinical outcomes of patients with inflammatory bowel disease: a systematic review and meta-analysis - Peiji Li; Yilin Wu; Wei Xiong; Jiahui Cao; Mengyun Chen; Zhaowei Yuan; Wenxin Guo; Bing Yang (BMC Gastroenterology)
Abstract Background Existing studies have explored the association between immune-inflammatory indices and inflammatory bowel disease (IBD), but there is a lack of comprehensive evidence. This meta-analysis and systematic review seeks to synthesize the data of available clinical research and offer the latest and comprehensive evidence-based conclusions regarding whether these immune-inflammatory indices can effectively predict the severity, activity, and prognosis of IBD. Methods Seven databases were comprehensively retrieved from their establishment to March 23, 2025. The combined results were described through standardized mean differences (SMD) or odds ratios (OR) with 95% confidence intervals (CI). Review Manager 5.4 and STATA 15.0 were leveraged for data analysis. Results Our analysis included 35 studies involving 5,870 patients. The aggregated data revealed that the neutrophil-to-lymphocyte ratio (NLR) (OR = 1.18, 95% CI:1.04 to 1.34; P = 0.001) (SMD = 1.01, 95%CI = 0.73 to 1.29, P < 0.001), platelet-to-lymphocyte ratio (PLR) (SMD = 0.60, 95%CI = 0.46 to 0.74, P < 0.001), neutrophil-to-platelet ratio (NPR) (OR = 1.20, 95% CI:1.08 to 1.32, P < 0.001), and C-reactive protein to albumin ratio (CRP/ALB) (OR = 1.50, 95% CI:1.38 to 1.65, P < 0.001) were potentially linked to disease activity in IBD patients. PLR (SMD = 1.08, 95%CI = 0.60 to 1.55, P < 0.001) showed potential associations with disease severity in IBD patients. Additionally, NLR (SMD = 0.43, 95%CI = 0.15 to 0.70, P = 0.002) and eosinophil-to-lymphocyte ratio (ELR) (SMD = 0.63, 95%CI = 0.26 to 1.00, P < 0.001) had potential associations with endoscopic response in IBD patients. Moreover, NLR was potentially associated with disease relapse(OR = 1.35, 95% CI:1.09 to 1.68; P = 0.006) and steroid responsiveness (SMD = 0.50, 95%CI = 0.15 to 0.85, P = 0.005). Conclusion NLR, PLR, NPR, and CRP/ALB are potential predictors of disease activity in IBD patients. PLR shows the potential to predict disease severity, while NLR and ELR are potential indicators of endoscopic response. Furthermore, NLR is also a potential predictor of relapse and steroid responsiveness. Currently, there is insufficient evidence to support an association between NLR and the severity of IBD, whereas lymphocyte-to-monocyte ratio (LMR) appears to be associated with both the severity and activity of IBD and PLR and eosinophil*neutrophil-to-lymphocytes ratio (ENLR) are associated with endoscopic response in IBD. PROSPERO registration CRD 42024609659.